Monetary Policy and Asset Price Bubbles: A Nonlinear Policy Rule - Alexander Mislin (Credit and Capital Markets – Kredit und Kapital, 2016)
The recent debate about asset price bubbles and monetary policy in view of "leaning against the wind" is controversial in economic literature. In this paper we argue that depending on the circumstances there is space for the central bank to lean against financial imbalances. With an optimal bounded control problem in continuous time we have developed an augmented nonlinear Taylor Rule. The main advantage of our formulation is its much greater analytical tractability, which produces distinct results. Even under the assumption of nonlinearities the central bank is in a position to move the interest rate above a threshold value to provide financial stability. – – Geldpolitik und Vermögenspreisblasen: Eine nichtlineare Politikregel Die jüngste Debatte um das Konzept des Gegensteuerns ("leaning against the wind") im Angesicht von Vermögenspreisblasen ist höchst kontrovers in der ökonomischen Literatur. In der vorliegenden Arbeit wird argumentiert, dass die Notenbank unter bestimmten Bedingungen einen Spielraum hat mit einer Politik des Gegensteuerns finanzielle Ungleichgewichte abzubauen. Mit einem optimalen Kontrollproblem in stetiger Zeit wird eine erweiterte nichtlineare Taylorregel ermittelt. Einer der wesentlichen Vorteile dieser Herangehensweise ist die analytische Nutzbarkeit, die differenzierte Ergebnisse erlaubt. Sogar unter der Annahme von Nichtlineartäten ist die Notenbank in der Lage den Zins oberhalb eines Schwellenwertes zu setzen, um Finanzstabilität zu gewährleisten.
Keywords: E52; E58; 330; monetary policy; financial stability